2006
DOI: 10.1902/jop.2006.050443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodontal Treatment on Serum C‐Reactive Protein Levels: A Systematic Review and Meta‐Analysis

Abstract: There is now a large body of evidence to indicate that systemic inflammation is present in patients with periodontal disease. Thus, information from RCTs and single-cohort studies does not support the hypothesis that periodontal treatment can reduce systemic CRP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 39 publications
5
89
1
4
Order By: Relevance
“…After reviewing all clinical trials, authors agreed to perform metaanalysis only on markers where sufficient data were available (Table 1). One biomarker had been recently extensively reviewed and more than one systematic review with metaanalysis had been already published (Ioannidou et al 2006, Paraskevas et al 2008, Freitas et al 2012. We therefore did not include it in a meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…After reviewing all clinical trials, authors agreed to perform metaanalysis only on markers where sufficient data were available (Table 1). One biomarker had been recently extensively reviewed and more than one systematic review with metaanalysis had been already published (Ioannidou et al 2006, Paraskevas et al 2008, Freitas et al 2012. We therefore did not include it in a meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, although very short-term effect was evaluated, the mean CRP levels at the end of evaluation period were almost similar to baseline values in both groups. Effect of periodontal treatment on CRP levels in longer periods, as mentioned elsewhere [1] was not evaluated. A third limitation of this study is the number of individuals included in this analysis is relatively small…”
Section: Discussionmentioning
confidence: 99%
“…ic periodontitis and elevated serum C-reactive Protein (CRP) levels [1]. However, in order to determine whether this increase was due to periodontal infections or not, the possible effects of periodontal therapy on CRP levels were also investigated in numerous studies [2,[3][4][5][6][7].…”
mentioning
confidence: 99%
“…It has been suggested that oral hygiene practices are responsible for spontaneous cases of bacteraemia. Such bacteraemias either from periodontal procedures or oral hygiene practices are of low-grade intensity (10 -200 CFU/ml of blood) and of short duration [15]. Bacteremia induced by Porphyromonas gingivalis (Pg) leads to intimal hyperplasia associated with overexpressions of embryonic isoform of myosin heavy chain and oral hematogenous spreading of Pg is a causative event in the development of aortic hyperplasia in periodontitis patients [56].…”
Section: Maharajmentioning
confidence: 99%
“…Periodontal therapy has had some success in the modification of many of inflammatory indicators in systemically healthy adults [15]. Thus we must make sure if periodontal intervention could lower the risk of cardiovascular events or even prevent onset and progression of the disease.…”
Section: Introductionmentioning
confidence: 99%